2020
DOI: 10.7150/ijbs.45710
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin facilitates ROS-induced apoptosis via the p38-MAPK/HSP27-mediated pathways in lung squamous cell carcinoma

Abstract: Lung squamous cell carcinoma (SCC) is one of the deadliest cancers both in China and worldwide. To date, the efficacy of lung SCC treatments is limited. Recent studies have elucidated the powerful anti-tumour role of dioscin in different human cancers. Here, our study aims to investigate the effect of dioscin on lung SCC and its underlying mechanism. First, we found that dioscin not only inhibited cell proliferation and cell migration and induced cell apoptosis in lung SCC cells but also suppressed tumour grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Further, the GO-terms ‘p38 MAPK-pathway’ and ‘Integrin signaling pathway’ were found to be enriched in serum treated hCSCs compared to untreated hCSCs [ 17 ]. In contrast, a recent study showed p38-MAPK and phosphorylated Hsp27 to mediate apoptosis of lung squamous cell carcinoma cells [ 32 ], suggesting a potential cell type-specific function of p38-MAPK and Hsp27. These findings also underline the necessity to investigate the molecular dynamics of migration in a cell type-specific manner.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Further, the GO-terms ‘p38 MAPK-pathway’ and ‘Integrin signaling pathway’ were found to be enriched in serum treated hCSCs compared to untreated hCSCs [ 17 ]. In contrast, a recent study showed p38-MAPK and phosphorylated Hsp27 to mediate apoptosis of lung squamous cell carcinoma cells [ 32 ], suggesting a potential cell type-specific function of p38-MAPK and Hsp27. These findings also underline the necessity to investigate the molecular dynamics of migration in a cell type-specific manner.…”
Section: Discussionmentioning
confidence: 90%
“…Hsp27 has been shown to be involved in F-actin assembly and migrative processes of vascular smooth muscle cells [ 30 , 31 ]. However, other studies demonstrated apoptosis of lung squamous cell carcinoma cells upon phosphorylation of Hsp27 [ 32 ], which indicates a potential cell type-specific function of Hsp27.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al observed that dioscin exerts its antitumor functions on SCC by studying tumor‐bearing mice treated with dioscin. Dioscin‐inhibited cell proliferation and migration, induced apoptosis and curtailed tumor growth in the mice by triggering the accumulation of intracellular ROS by activating the p38‐MAPK/HSP27‐mediated pathway 62 …”
Section: Anticancer Mechanisms Of Dioscinmentioning
confidence: 99%
“…ROS is a subproduct of oxidative energy metabolism and normally controls cell proliferation, differentiation, migration, and death. 62 This dioscin-induced ROS accumulation results in unfavorable changes in cancerous tissue such as DNA damage, structural changes and mitochondrial dysfunction. ROS is responsible for activating different apoptotic pathways to ensure the termination of tumor growth.…”
Section: Other Anticancer Activities Of Dioscinmentioning
confidence: 99%
See 1 more Smart Citation